Nordic Walking and Functional Outcomes in Individuals with Type 2 Diabetes - Szmeja, Sebastian; Wysokiński, Piotr; Masalska, Julia; Toczydłowski, Kacper Robert; Mazek, Natalia; Król, Paweł Adam; Michalik, Martyna; Mamczak, Maria; Klimas, Paweł; Strzępek, Stanisław Ferdynand (Quality in Sport, 2026)
Introduction and aim: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by impaired glucose regulation and insulin resistance. Physical activity plays a key role in its management. Nordic walking, involving the use of poles, may enhance exercise intensity and therapeutic effects. The aim of this study was to evaluate its impact on functional and metabolic outcomes in individuals with T2DM. Material and methods: This qualitative literature review is based on randomized controlled trials, systematic reviews, and meta-analyses. The analysis included studies involving adults with T2DM performing Nordic walking or structured walking interventions. Outcomes included HbA1c, VO₂max, body weight, BMI, muscle strength, and quality of life. Results: Nordic walking is associated with improved glycemic control, reduced HbA1c, body weight, and BMI, as well as enhanced insulin sensitivity. It also contributes to increased aerobic capacity, physical fitness, and functional performance. Additional benefits include improved body composition and quality of life. In some studies, Nordic walking demonstrated greater effectiveness than regular walking. Conclusions: Nordic walking is a safe and effective form of physical activity for individuals with T2DM. It supports improvements in metabolic and functional outcomes and can be recommended as part of comprehensive non-pharmacological management.